Editorial: CALJ in a trajectory of commitment to enlighten language teaching practices towards social transformation and hope - Journal, Colombian Applied Linguistics (Colombian Applied Linguistics Journal, 2020)
The Colombian Applied Linguistics Journal has been a space for encouraging language teacher researchers to share their experiences and illuminate others’ experience. In this trajectory, applied linguistics and English language teaching have been intertwined fields, where the integration of theoretical tools has allowed new comprehensions of one another. Authors of the journal have demonstrated this mutual exchange with the multiple outlooks and topics that they have proposed as part of their writings. As mentioned in the previous editorial (CALJ, Vol. 21, Nº 2, 2019), applied linguistics has been useful to determine not only a variety of practices of language teaching and learning, but also the implication of those in broader areas (Quintero & Bonilla, 2020, p. 2). In the same line of thought, the reflections that have emerged in the process of language teaching and learning have originated new inquiries in applied linguistics that have further contributed to both fields. In the commitment that the Colombian Applied Linguistics Journal has taken on, authors continue to explore areas that have a variety of characteristics.